Ultrastructural Morphology of the Antenna and Maxillary Palp of Sarcophaga tibialis (Diptera: Sarcophagidae). Issue 4 (1st May 2016) - Pezzi, M.; Whitmore, D.; Chicca, M.; Semeraro, B.; Brighi, F.; Leis, M.
Abstract: A scanning electron microscopy investigation of the antenna and maxillary palp of the adult of Sarcophaga tibialis Macquart (Diptera: Sarcophagidae), a species of medical, veterinary, and forensic relevance, is presented for the first time. Adults of both sexes used in this study were obtained from larvae collected in a case of traumatic myiasis in a domestic cat in northern Italy. The antenna of S. tibialis is that typical of cyclorrhaphan Diptera, consisting of three segments: the scape, the pedicel, and the postpedicel, bearing the arista. The scape is covered by microtrichia and has a row of long chaetic sensilla. The pedicel is also covered by microtrichia and has three types of chaetic sensilla and a cluster of setiferous plaques. Trichoid, styloconic, clavate, and basiconic sensilla are distributed among the microtrichia on the postpedicel. Invaginated basiconic-like sensilla and olfactory pits are also present, the latter ones more numerous in the female. Our results are compared with those obtained for other calyptrate flies, mainly in the family Sarcophagidae. The data obtained may represent a basis for electrophysiological studies on the sensorial activity of the species related to the search for food sources, mates, and suitable larviposition sites, and for comparative morphological studies with other Diptera.